University as a place to cultivate leadership traits - Nurul Maherah - Shalfarina, Shahriman (2022)
KUANTAN, 17 March 2022 – Leadership needs to be cultivated in individuals in order to produce people who are confident, wise in planning and able to encourage others to do something to achieve the objectives set.